Efektivitas Alat Tangkap Pancing Tonda Taba-taba pada Penangkapan Ikan Karang di Desa Tontayuo Kecamatan Batudaa Pantai Kabupaten Gorontalo - Bahari, Yunus A; Baruadi, Alfi Sahri; Fachrussyah, Zhulmaydin Chairil (The NIKe Journal, 2024)
This research was carried out in Tontayuo Village, Batudaa Pantai District, Gorontalo Regency. This research aims to describe the construction of the Taba-taba trolling fishing gear and measure its effectiveness. The research was carried out using observation methods and calculating the results of fishermen's catches. The taba-taba trolling fishing equipment and how to operate it are by jerking it and pulling it by a boat. The operating method consists of a line, hook, artificial bait, swivel, and without using weights. This taba-taba fishing rod is a type of traditional fishing gear that is often used by fishermen to catch coral fish at night. The taba-taba trolling fishing gear according to the criteria of Syari et al. (2014) is very effective in catching squirrel's eye fish because it has effectiveness (60.76%), and less effective in catching swanggi fish (effectiveness 26.75%), while for catching glaga fish taba-taba fishing rods are less effective because they only have effectiveness (14 .58%).